ANALISIS FUNGSI SHUUJOSHI YO DAN NE DALAM KOMIK DORAEMON - R.Dinia Utari; Nana Rahayu; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT This study about function of shuujoshi yo and ne. Author is used comic Doraemon volume 12, 13 and 14 as data. Which aims to find out the function of shuujoshi yo and shuujoshi ne and what function is always using in conversation. The methods used in this research is descriptive method. In analyzing the data, the author analyze every sentence which added with shuujoshi yo or shuujoshi ne. The results showed the function of shuujoshi yo had 9 functions, and shuujoshi ne had 9 functions. All of this functions the most sentences which always being added with shuujoshi is when speaker want to show the expression or feeling. Keywords : joshi, shuujoshi yo, shuujoshi ne, analyze, sentence function, doraemon